Semantics sentence and information structure - Portner, Paul; Maienborn, Claudia; Heusinger, Klaus von (Mouton reader., 2019)
Read this book to get a deeper understanding of a wide range of semantics research on complex sentences and meaning in discourse. These in-depth articles from leading names in their fields cover the core concepts of sentential semantics such as tense, modality, conditionality, propositional attitudes, scope, negation, and coordination. The highly cited material, covers questions, imperatives, copular clauses, and existential sentences. It also includes essential research on sentence types, and explains central concepts in the theory of information structure and discourse structure, such as topics, cohesion and coherence, accessibility and discourse particles.